2020
DOI: 10.3390/cancers12061705
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Tyrosine Kinase Receptor TIE-1 as Novel Therapeutic Target in High-PI3K-Expressing Ovarian Cancer

Abstract: Tyrosine kinase receptor TIE-1 plays a critical role in angiogenesis and blood-vessel stability. In recent years, increased TIE-1 expression has been observed in many types of cancers; however, the biological significance and underlying mechanisms remain unknown. Thus, in the present study, we investigated the tumor biological functions of TIE-1 in ovarian cancer. The treatment of SKOV3 ovarian-cancer cells with siRNA against TIE-1 decreased the expression of key molecules in the PI3K/Akt signaling pathway, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…4 B, C). Since FLI1 regulates the expression of its target genes by binding to their promoter regions, we explored whether it directly modulated the expression of TIE1, which has been reported to promote XPC-dependent nucleotide excision repair (NER) and chemotherapy resistance [ 38 ]. hTFtarget ChIP-seq database also indicated that FLI1 might transcriptionally regulate TIE1 by binding to its promoter region (Additional file 3: hTFtarget ChIP-seq data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 B, C). Since FLI1 regulates the expression of its target genes by binding to their promoter regions, we explored whether it directly modulated the expression of TIE1, which has been reported to promote XPC-dependent nucleotide excision repair (NER) and chemotherapy resistance [ 38 ]. hTFtarget ChIP-seq database also indicated that FLI1 might transcriptionally regulate TIE1 by binding to its promoter region (Additional file 3: hTFtarget ChIP-seq data).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that PI3K/AKT signaling pathway is associated with radioresistance of cancers [ 40 42 ]. TIE1 has been reported to be related to the PI3K/AKT signaling pathway in ovarian cancer [ 38 ]. KEGG pathway analysis indicated that FLI1 regulated PI3K/AKT signaling pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations